MYTHOPOEIC ONOMASTICS: A TAXONOMIC PARADIGM FOR MYTHONYMIC CONSTRUCTION IN C.S.LEWIS'S LITERARY CORPUS (Scientific journal of the Fergana State University, 2026)
This article identifies 276 mythological names (mythonyms) in C.S.Lewis’s works through philological, narratological, and other analytical methods, classifying them into five categories. The analysis reveals that while Lewis initially used mythonyms for simple linguistic transformations, he later employed them to convey complex symbolic layers. The findings highlight his approach to harmonizing mythology with religious theology.